2003
DOI: 10.1055/s-2000-132
|View full text |Cite
|
Sign up to set email alerts
|

Does Hyperbaric Oxygen Enhance the Effect of Photodynamic Therapy in Patients with Advanced Esophageal Carcinoma? A Clinical Pilot Study

Abstract: Combined PDT/HBO represents a new approach in the treatment of esophageal cancer which, in this pilot study, appears to have enhanced the efficiency of PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…In photodynamic therapy, molecular oxygen is a crucial factor for hematoporphyrin‐derivative photodynamic activity in vitro (4,16). By absorption of light, photosensitizers are excited to an energetic state and indirectly react with molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In photodynamic therapy, molecular oxygen is a crucial factor for hematoporphyrin‐derivative photodynamic activity in vitro (4,16). By absorption of light, photosensitizers are excited to an energetic state and indirectly react with molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent literature, several experimental studies have confirmed the positive effect of PDT combined with HBO, which may help to enhance the therapeutical effect of PDT in case of advanced esophageal cancer, cancer of the GEJ and in patients with malignant tracheo-bronchial stenosis suffering from progressive lung cancer [6,7,[37][38][39]. By the help of supportive HBO, satisfactory reduction of the endoluminal tumor load can be achieved and it helps conditioning the patient for further palliative treatment procedures.…”
Section: Discussionmentioning
confidence: 92%
“…According to those animal-based studies, experimental clinical pilot studies in human patients suffering from different thoracic malignancies were conducted [6,7,16,[37][38][39]. Those promising results suggested that HBO in PDT might accelerate the photodynamic reaction by raising the transmission efficiency of light energy, increasing the quantum amount of oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations